2020
DOI: 10.1177/0361198120947421
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Framework for Freeway Speed Prediction in Adverse Weather

Abstract: The introduction of deep learning (DL) models and data analysis may significantly elevate the performance of traffic speed prediction. Adverse weather causes mobility and safety concerns because of varying traffic speeds with poor visibility and road conditions. Most previous modeling approaches have not considered the heterogeneity of temporal and spatial data, such as traffic and weather conditions. This paper presents a framework, consisting of two DL models, to predict traffic speed under normal conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…Many deep learning methods, such as LSTM, Gated Recurrent Unit (GRU), Bi-directional Long Short Term Memory (Bi-LSTM), Bi-Gated Recurrent Unit (Bi-GRU) and Graph Convolution Network (GCN) are similar to the RNN structure, which has been widely applied to predict time sequence information. LSTM is an advanced RNN structure, which is robust for predicting bus travel time [19,20]. Liu et al [32] developed an LSTM model to predict bus travel time using GPS data and found that LSTM outperformed RNN.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many deep learning methods, such as LSTM, Gated Recurrent Unit (GRU), Bi-directional Long Short Term Memory (Bi-LSTM), Bi-Gated Recurrent Unit (Bi-GRU) and Graph Convolution Network (GCN) are similar to the RNN structure, which has been widely applied to predict time sequence information. LSTM is an advanced RNN structure, which is robust for predicting bus travel time [19,20]. Liu et al [32] developed an LSTM model to predict bus travel time using GPS data and found that LSTM outperformed RNN.…”
Section: Methodsmentioning
confidence: 99%
“…Recurrent Neural Network (RNN) considers a sequence of data inputs and has been widely used in time sequence analysis. The LSTM is an advanced form of RNN, which is robust for predicting bus travel time [19,20]. However, LSTM is characterised by a set of hyperparameters, which shall be effectively determined by a sound algorithm to yield the best performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The average speed [ ( )] TT t x x  and the travel time from the origin node to destination ( ; , ) TT t O D can be calculated by equation (14) and equation (15).…”
Section: ˆ[ () ]mentioning
confidence: 99%
“…The travel time of each link was calculated according to equation (14), and the travel time from the origin node to the destination was calculated according to equation (15).…”
Section: Model Solvingmentioning
confidence: 99%
See 1 more Smart Citation